Poverty in Israel - Dirk Michel; Claudia Schertges (Social Work and Society, 2007)
The paper deals with poverty within Israel. Against the background of the history of pre-state Israel and the developments after the establishment of the State of Israel in 1948 the historical roots of Israeli poverty are analyzed. Thus the 'socialist'-Zionist project, ethnic exclusion, religious and intra-Jewish ethnic lines of conflict as well as the Bedouins, Druzes and Israeli Arabs as 'specific' Israeli citizen are discussed.